2019
DOI: 10.3390/pathogens8040200
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Phylogenetic Analysis of Infectious Hematopoietic Necrosis Virus Strain SNU1 Isolated in Korea

Abstract: Infectious hematopoietic necrosis virus (IHNV), one of the most important pathogenic fish viruses, affects trout fisheries and causes considerable economic losses. Currently, in Korea, more studies on IHNV infection are being reported. However, relatively less data is available on Korean isolates than on those from other countries. Few studies have focused on gene sequence analyses of IHNV glycoprotein (G) gene and almost none have focused on other gene fragments. Therefore, considering the dearth of adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…4. Discussion Numerous viral diseases, such as RSIV infection, VHS, VER, IHN, SVC, and LCDV have been reported as critically important in the South Korea aquaculture industry (Cho et al, 2010;Hossain et al, 2007;Kim et al, 2018;Oh et al, 2019). RSIV infection is a viral disease that causes massive mortality in rock bream mariculture.…”
Section: Evaluation Of Newly Designed Multiplex Pcr Using Field Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Discussion Numerous viral diseases, such as RSIV infection, VHS, VER, IHN, SVC, and LCDV have been reported as critically important in the South Korea aquaculture industry (Cho et al, 2010;Hossain et al, 2007;Kim et al, 2018;Oh et al, 2019). RSIV infection is a viral disease that causes massive mortality in rock bream mariculture.…”
Section: Evaluation Of Newly Designed Multiplex Pcr Using Field Samplesmentioning
confidence: 99%
“…Further, specificity and sensitivity are the most important aspects when designing a primer pair (Dieffenbach et al, 1993). Based on previous studies, the sequence analysis of different genotypes was performed, and it was shown that the genotype TRBIV has a low identity compared to other genotypes (Supplementary table 1) Oh et al, 2019). The new multiplex PCR primers were designed by selecting the gene with specific characteristics among the genotypes.…”
Section: Evaluation Of Newly Designed Multiplex Pcr Using Field Samplesmentioning
confidence: 99%